Microbiological evaluation of the meat from young collared peccaries (Pecari tajacu Linnaeus, 1758) (Research, Society and Development, 2021)
The increased demand for meat from wild animals for human consumption, as an alternative protein source, brings with it the need for research that demonstrates the quality of such product. The technical information about the meat from collared peccaries still needs studies and aiming to collaborate with the already existing knowledge, this research had as its objective to provide subsidies for evaluation of the sanitary quality of the meat from collared peccaries. Twelve animals were used, six males and six females, aged four to five months, from the breeding stock of the Federal Rural University of the Semi-Arid and, after euthanasia by a slaughter technique used in goats, the meat samples were collected through sterile swabs at the locations of the hind leg, loin, belly and axilla of each animal, totaling 48 samples. The maximum mesophilic count found was 1.9 x 103 CFU/ml, the total coliform and thermotolerant coliform counts were below the one determined in the legislation for meat from domestic animals, however, through biochemical tests, the presence of E. coli from the biotype 1 and biotype 2 was found, in seven and six samples, respectively. Search results for Salmonella spp. were negative in all samples and, as for Staphylococcus spp., only one sample had the count above the level allowed by law. The contamination load related to the bacteria E. coli proved to be high, making 13 samples unfit for consumption. Regarding the other data, the meat from young collared peccaries showed a low contamination load.